PEMBENTUKAN NORMA AMBANG BATAS PARLEMEN DALAM PERSPEKTIF TEORI KRITIS JURGEN HABERMAS - Sholahuddin Al-Fatih (Universitas Muhammadiyah Malang, 2020)
This study tries to discuss the formation of parliamentary threshold norms in the perspective of Jurgen Habermas' critical theory. Through historical, conceptual and statutory approaches, this research attempts to examine prescriptively the dynamics of implementing parliamentary thresholds in legislative elections. This research makes the thinking of Jurgen Habermas and the thinkers around him as a benchmark and analysis. The results of this study indicate that the formation of norms and the application of parliamentary thresholds in elections based on the perspective of Jurgen Habermas's critical theory are appropriate because they do not only look at the legal aspect, but from the needs and interpretations based on other sciences. This research is expected to be able to help academics and legal practitioners, especially regarding electoral law, to be able to dig deeper into the perspective of law and its integration with other disciplines, not only from one or two experts, but from several other experts.